Study on Polypharmacy in Patients with Cardiovascular Diseases - Md. Mamun Al-Amin, Artyom Zinchenko Md. Sohel Rana, Mir Muhammad Nasir Uddin, Mst. Shahnaj Pervin (Journal of Applied Pharmaceutical Science)
We analyzed the prevalence of polypharmacy among cardiac patients in the Natioal Institute of Cardiovascular Diseases of Dhaka, Bangladesh. Polypharmacy was defined as consumption of six or more drugs at the same time. We entered the drugs that were prescribed into the Drug Interaction Checker provided by MedScape online edition. Almost 85% of cardiac patients met criteria for three types of polypharmacy (minor, moderate and serious). However, serious and moderate types of polypharmacy were not influnenced by the increase in number of disorders (polymorbidity) as well as by the total number of drugs taken. The most frequent cause and threat that is associated with polypharmacy comes primarily from the quality of drug-drug interactions and not the total number of drugs prescribed. Most of the dangerous consecuences of polypharmacy came from the interaction of Clopidogrel with either Aspirin or PPIs. Our study emphasizes the need of informing doctors more about the problem of polypharmacy. Careful and thoughtful drug prescription strategy seems to be able to eliminate most of the cases of polypharmacy even in patients who are suffering from a multiplace disorders simultaneously. The results also provide support for development of new drugs that take into account compatibility with other medication, especially in elderly people.
Keywords: Polypharmacy,Drug Interaction,Polymorbidity,Clopidogrel,Cardiovascular Disease.